Keluhan Kesehatan Pernafasan Pada Driver Ojek Online di Medan - Agnes Ferusgel; Aquina Widya (Dian Nuswantoro Semarang, 2019)
ABSTRACTÂ Objective : One of the groups of informal workers that is quite a trend now is beingâ€ ojek onlineâ€. In this case, as the driver, can face the of experiencing workplace accidents and work-related illnesses due to a disordered work system. The working environment of ojek online filled with dust, steam, and pollutant gases can risk disrupting health can has breathing disorders. The objektive ofÂ this research deal to describe the factors that influence respiratory complaints in â€œojek online in Medan. Method : This research used quantitative method. Sample size in this study were 40 respondents. The Data was analyzed by using multiple logistic regression. Result : The results explained the factors affecting respiratory complaints on ojek online drivers in Medan were workload (sig= 0.017), duration of work (sig= 0.049) and mask use (sig= 0.023). It is expected to manage work time independently and always use a mask when working to reduce dust and air pollutant exposure while in the work environment.Â Keywords : workload, respitory complaints, ojek online drivers